2017
DOI: 10.1515/cpp-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-resistant schizophrenia – non pharmacological augmentation methods

Abstract: Clozapine is the drug of choice for drug-resistant schizophrenia, but despite its use, 30-40% patients fail to achieve satisfactory therapeutic effects. In such situations, augmentation attempts are made by both pharmacological and non-pharmacological methods. To date, most of the work has been devoted to pharmacological strategies, much less to augemantation of clozapine with electroconvulsive therapy (C+ECT), transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS).Aim: The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(238 reference statements)
0
1
0
Order By: Relevance
“…Some of the more recent reviews have concluded that electroconvulsive therapy (ECT) is an effective augmentation strategy, especially when medications fail to decrease persistent positive symptoms[ 2 , 8 , 20 , 46 , 51 ]. However, this conclusion appears to be based on a single meta-analysis of 18 RCTs[ 52 ], which showed that the ECT-clozapine combination was better than clozapine alone in reducing positive symptoms.…”
Section: Augmentation Strategies For Crs: a Brief Reviewmentioning
confidence: 99%
“…Some of the more recent reviews have concluded that electroconvulsive therapy (ECT) is an effective augmentation strategy, especially when medications fail to decrease persistent positive symptoms[ 2 , 8 , 20 , 46 , 51 ]. However, this conclusion appears to be based on a single meta-analysis of 18 RCTs[ 52 ], which showed that the ECT-clozapine combination was better than clozapine alone in reducing positive symptoms.…”
Section: Augmentation Strategies For Crs: a Brief Reviewmentioning
confidence: 99%